Respuesta :

Hello!

The answer is:

The simplified form of the given expression is 7.

[tex]49^{\frac{1}{2}}=\sqrt[2]{49^{1}}=\sqrt[2]{49}=7[/tex]

Why?

To simplify the given expression, we must remember the following property of roots:

[tex]a^{\frac{m}{n}}=\sqrt[n]{a^{m} }[/tex]

We are given the expression:

[tex]49^{\frac{1}{2}}[/tex]

Which can be also written as:

[tex]49^{\frac{1}{2}}=\sqrt[2]{49^{1}}=\sqrt[2]{49}[/tex]

Then, simplifying we have:

[tex]\sqrt[2]{49}=7[/tex]

Hence, the simplified form of the given expression is 7.

Have a nice day!

Answer: 7

Step-by-step explanation: To simplify [tex]49^{1/2}[/tex], it's important to understand that an exponent of 1/2 means that we take the square root of the base. In other words, [tex]49^{1/2}[/tex] means the same thing as the square root of 49 or [tex]\sqrt{49}[/tex] and the square root of 49 is 7.

This means that [tex]49^{1/2}[/tex] is 7.

Ver imagen TheBlueFox